Parotidektomi radikal pada karsinoma sel asinus parotis - Marlinda Adham; Meila Sutanti (Oto Rhino Laryngologica Indonesiana, 2010)
Background: Acinic cell carcinoma is an uncommon type of parotid malignant tumour. One commonsymptom of this low grade malignancy is slowly growing parotid mass. Pain in parotid area and facialnerve paresis are important symptoms that indicate malignancy. From clinical manifestations, it is difficultto differentiate between this kind of malignancy with benign parotid tumour. Fine needle aspiration biopsyand CT scan are important in diagnosing acinic cell parotid carcinoma, and surgery is the main therapy.Purpose: We present this case to enlighten general practitioners and also otorhinolaryngologists aboutthis kind of parotid malignancy that has similar presentation with benign parotid tumour. Case: Onecase of acinic cell carcinoma of the parotis was reported. A 53 years old man was diagnosed as stage IVacinic cell carcinoma. Case management: The patient underwent radical parotidectomy. He was plannedfor chemotherapy and radiotherapy but untill now, he still refused further treatment. Conclusion: Aciniccell carcinoma is one of malignant tumour that has a good prognosis, especially if diagnosed early andadequately treated.Key words: malignant parotid tumour, acinic cell carcinoma, fine needle aspiration biopsy,parotidectomy.Abstrak : Latar belakang: Karsinoma sel asinus adalah salah satu tipe keganasan kelenjar liur yang jarang sekaliterjadi. Karsinoma ini bersifat low grade yang ditandai oleh benjolan pada daerah parotis yang tumbuhsecara lambat. Dari pemeriksaan klinis, keganasan ini sulit dibedakan dengan tumor jinak. Salah satugejala yang membedakan dari tumor jinak adalah rasa nyeri dan paresis nervus fasialis. Pemeriksaan biopsiaspirasi jarum halus dan tomografi komputer dapat menegakkan diagnosis karsinoma parotis jenis ini.Terapi utamanya adalah parotidektomi. Tujuan: Kasus ini diajukan agar para dokter umum dan dokterspesialis Telinga, Hidung, Tenggorok dapat mengenali adanya karsinoma parotis yang bermanifestasiklinis seperti tumor jinak ini. Kasus: Dilaporkan satu pasien, laki-laki berusia 53 tahun yang didiagnosiskarsinoma sel asinus kelenjar parotis stadium IV. Penatalaksanaan: Pada pasien ini dilakukan operasiparotidektomi radikal dan direncanakan untuk radiasi dan kemoterapi. Sampai saat ini, pasien masihmenolak untuk tatalaksana lebih lanjut pascabedah.Kesimpulan: Karsinoma sel asinus merupakan kasuskeganasan yang memiliki prognosis baik, terutama jika didiagnosis dini dan diterapi secara adekuat.Kata kunci: tumor ganas parotis, sel asinus, biopsi aspirasi jarum halus, parotidektomi.